2017
DOI: 10.1111/radm.12276
|View full text |Cite
|
Sign up to set email alerts
|

Service innovation in times of economic crisis: the strategic adaptation activities of the topE.U.service firms

Abstract: This article examines the long‐term strategic adaptation activities top service firms use to respond to economic crisis. Based on a longitudinal dataset of 97 leading European service firms, it empirically conceptualizes three clusters or strategic types of organizational response to overcome long‐term financial strain experienced during 2008–2011, it tests the survivability of their strategic orientation and it assesses their relationship with organizational performance during the crisis (2008–2011) and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…More specifically, by adjusting Fromhold-Eisebith's framework for service firms, this study develops a conceptual framework that illustrates resilience-building strategies, success factors, and resources that may help service firms to survive, recover, and grow during and after the COVID-19 pandemic. In previous economic disruptions, service firms that had a continuous commitment to expansion by adopting resilience-building strategies showed long-term survivability and growth in operating profits and market capitalization (Martin-Rios & Pasamar, 2018). The following sub-sections discuss these strategies.…”
Section: Resilience-building Strategies For Service Firmsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, by adjusting Fromhold-Eisebith's framework for service firms, this study develops a conceptual framework that illustrates resilience-building strategies, success factors, and resources that may help service firms to survive, recover, and grow during and after the COVID-19 pandemic. In previous economic disruptions, service firms that had a continuous commitment to expansion by adopting resilience-building strategies showed long-term survivability and growth in operating profits and market capitalization (Martin-Rios & Pasamar, 2018). The following sub-sections discuss these strategies.…”
Section: Resilience-building Strategies For Service Firmsmentioning
confidence: 99%
“…Thus, this study responds to this need by addressing an individual firm's resilience. Also, due to the lack of research on service firms' responses to a crisis (Borchert & Mattoo, 2010;Martin-Rios & Pasamar, 2018), the current study merely focuses on service firms. More specifically, by adjusting Fromhold-Eisebith's framework for service firms, this study develops a conceptual framework that illustrates resilience-building strategies, success factors, and resources that may help service firms to survive, recover, and grow during and after the COVID-19 pandemic.…”
Section: Resilience-building Strategies For Service Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lome et al (2016) in a study of Norwegian companies indicated that firms devoting significant resources in R&D after the 2000 financial crisis performed better relative to firms that seized such projects. Such findings have been verified by Martin-Rios and Pasamar (2018) and Nemlioglu and Mallick (2017) in the European Union and United Kingdom, respectively.…”
Section: Introductionmentioning
confidence: 55%
“…Creativity and innovation are considered important antecedents of competitive advantages, especially for restaurants [ 2 , 12 , 36 ]. Therefore, the crisis could even increase some restaurants’ performance [ 74 ]. P2: In the next five to ten years, crises like the corona virus pandemic will significantly increase creativity and innovation in haute cuisine restaurants.…”
Section: Methodsmentioning
confidence: 99%